2002
DOI: 10.1083/jcb.200112023
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of human DNA topoisomerases IIα and IIβ in living cells

Abstract: DNA topoisomerase (topo) II catalyses topological genomic changes essential for many DNA metabolic processes. It is also regarded as a structural component of the nuclear matrix in interphase and the mitotic chromosome scaffold. Mammals have two isoforms (α and β) with similar properties in vitro. Here, we investigated their properties in living and proliferating cells, stably expressing biofluorescent chimera of the human isozymes. Topo IIα and IIβ behaved similarly in interphase but differently in mitosis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
196
2
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(227 citation statements)
references
References 44 publications
(84 reference statements)
24
196
2
2
Order By: Relevance
“…Live-cell experiments with dyed topo II (Swedlow et al 1993) and GFP fusion proteins (Christensen et al 2002, Tavormina et al 2002 disagree as to the degree of its axial localization. Swedlow et al (1993), Sumner (1996) have suggested that topo II will be found where DNA interlocks occur, which in conjunction with topo II_s dynamic exchange on and off chromosomes might be responsible for the variability in axial localization observed experimentally.…”
Section: Large-scale Mitotic Chromosome Organizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Live-cell experiments with dyed topo II (Swedlow et al 1993) and GFP fusion proteins (Christensen et al 2002, Tavormina et al 2002 disagree as to the degree of its axial localization. Swedlow et al (1993), Sumner (1996) have suggested that topo II will be found where DNA interlocks occur, which in conjunction with topo II_s dynamic exchange on and off chromosomes might be responsible for the variability in axial localization observed experimentally.…”
Section: Large-scale Mitotic Chromosome Organizationmentioning
confidence: 99%
“…Metazoan cells contain topo IIa and b isoforms; during mitosis topo IIa is mainly resident on chromosomes, while topo IIb is mainly cytoplasmic (Meyer et al 1997). Observations of GFP-topo IIa fusion proteins in vivo show it to rapidly exchange on and off chromosomes (Christensen et al 2002, Tavormina et al 2002. Estimates for amounts on mitotic chromosomes vary over the range of one topo IIa for every 20Y50 kb of DNA (Gasser et al 1986, Fukui & Uchiyama 2007.…”
Section: Topoisomerase IImentioning
confidence: 99%
“…Although both human isoforms can complement yeast TOP2 mutants (Jensen et al, 1996), only the ␣ isoform is abundantly associated with chromosomes throughout mitosis (Christensen et al, 2002), particularly at centromeres (Rattner et al, 1996;Christensen Article published online ahead of print. Mol.…”
Section: Introductionmentioning
confidence: 99%
“…Complementation would be particularly valuable for the analysis of the numerous phosphoryation sites in topoII␣, which have variously been implicated in controlling topoII␣ activity, resistance to inhibition, and subcellular localization, but whose true physiological significance remains untested (Isaacs et al, 1998;Chikamori et al, 2003). Similarly, the ability of biofluorescent topoII␣ (topoII␣GFP) derivatives to complement topoII␣-deficient cells could be tested, providing a necessary adjunct to recent important studies of topoII␣GFP dynamics (Christensen et al, 2002;Tavormina et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation